2018
DOI: 10.1109/lmwc.2018.2869285
|View full text |Cite
|
Sign up to set email alerts
|

Low-Loss, High-Linearity RF Interposers Enabled by Through Glass Vias

Abstract: This is the accepted version of a paper published in IEEE Microwave and Wireless Components Letters. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Being inexpensive, transparent, electrically insulating, chemically inert, biocompatible, of high mechanical stiffness, and reusable, glass is a natural choice for the fabrication of interposing layers [30]. For example, it was recently shown that the use of TGVs can lead to low-loss and high-linearity radio frequency interposers [31]. Moreover, the properties of glass are strongly tunable.…”
Section: Introductionmentioning
confidence: 99%
“…Being inexpensive, transparent, electrically insulating, chemically inert, biocompatible, of high mechanical stiffness, and reusable, glass is a natural choice for the fabrication of interposing layers [30]. For example, it was recently shown that the use of TGVs can lead to low-loss and high-linearity radio frequency interposers [31]. Moreover, the properties of glass are strongly tunable.…”
Section: Introductionmentioning
confidence: 99%
“…Another disadvantage can be found in nonlinearity of conventional TSVs through the formation of a metal-oxidesemiconductor capacitor. Hence, silicon substrates are very unfavorable for high-linearity and low-insertion loss RF applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to resolve these challenges, glass substrate with through glass vias (TGVs) has recently been used for the packaging substrate or interposers for high-frequency applications [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Glass, as a substrate material, is emerging because of its low electrical loss, ability to form fine-pitch metal lines and spaces, machineability to create micro-size TGVs, high dimensional stability, a closely matched coefficient of thermal expansion (CTE) to silicon dies, and productivity in thin and large panels.…”
Section: Introductionmentioning
confidence: 99%